Optimal Defense Theory in an ant–plant mutualism: Extrafloral nectar as an induced defence is maximized in the most valuable plant structures. (3rd August 2020) - Calixto, Eduardo Soares; Lange, Denise; Bronstein, Judith; Torezan‐Silingardi, Helena Maura; Del‐Claro, Kleber
Abstract: Plants allocate defences in order to decrease costs and maximize benefits against herbivores. The Optimal Defense Theory (ODT) predicts that continuously expressed (i.e. constitutive) defences are expected in structures of high value, whereas defences that are expressed or that increase their expression only after damage or upon risk of damage (i.e. induced defences) are expected in structures of low value. Although there are several studies evaluating ODT predictions, few studies have successfully tested them as a way of measuring ecological investment in extrafloral nectary (EFN)‐mediated ant–plant interactions. Here we compared extrafloral nectar production and ant attractiveness to EFNs located on vegetative versus reproductive plant structures on Qualea multiflora plants subjected to different levels of simulated herbivory. We then addressed the following predictions emerging from the ODT: (a) extrafloral nectar produced in inflorescence EFNs will have higher volumes and calories and will attract more ants than extrafloral nectar produced in leaf EFNs; (b) extrafloral nectar production (volume and calories) and ant attendance will increase after simulated herbivory in leaf EFNs but not in inflorescence EFNs; (c) higher simulated leaf herbivory will induce higher extrafloral nectar production in EFNs on leaves and (d) more attractive extrafloral nectar (higher volume and calories) will attract more ants. Extrafloral nectar volume and calorie content, as well as ant abundance, were higher in EFNs of inflorescences compared to EFNs of leaves both before and after simulated herbivory, consistent with one of our predictions. However, EFNs on both leaves and inflorescences, not on leaves only, were induced by simulated herbivory, a pattern opposite to our prediction. Plants subjected to higher levels of leaf damage produced more and higher calorie extrafloral nectar, but showed similar ant abundance. Finally, more attractive extrafloral nectar attracted more ants. Synthesis . Our results show that extrafloral nectar production before and after simulated herbivory, as well as ant recruitment, varies according to the plant structure on which EFNs are located. Our study is the first to show that ant recruitment via extrafloral nectar follows predictions from Optimal Defense Theory, and that the ant foraging patterns may be shaped by the plant part attacked and the level of damage it receives. Abstract : Our results show that extrafloral nectar production before and after simulated herbivory, as well as ant recruitment, varies according to the plant structure on which EFNs are located. Our study is the first to show that ant recruitment via extrafloral nectar follows predictions from Optimal Defense Theory, and that the ant foraging patterns may be shaped by the plant part attacked and the level of damage it receives. Resumo: Plantas alocam defesas de maneira a reduzir custos e maximizar benefícios contra herbívoros. A Teoria da Defesa Ótima (TDO) prevê que as defesas expressas continuamente (ou seja, constitutivas) são alocadas em estruturas de alto valor, enquanto que as defesas expressas ou que aumentam sua expressão somente após dano ou sob risco de dano (defesa induzida) são alocadas em estruturas de baixo valor. Embora existam vários estudos avaliando as previsões da TDO, poucos estudos as testaram com sucesso como uma forma de medir o investimento ecológico nas interações formiga‐planta mediadas por nectários extraflorais (NEFs). Nesse estudo, nós comparamos a produção de néctar extrafloral e a atratividade das formigas aos NEFs localizados nas estruturas vegetativas versus reprodutivas de Qualea multiflora submetidas a diferentes níveis de simulação de herbivoria. Para isso, nós delineamos as seguintes previsões emergentes da TDO: (i) o néctar extrafloral produzido nos NEFs de inflorescências terá maiores valores de volume e caloria e atrairá mais formigas do que o néctar extrafloral produzido nos NEFs foliares; (ii) a produção de néctar extrafloral (volume e calorias) e a abundância de formigas aumentarão após simulação de herbivoria nos NEFs foliares, mas não nos NEFs de inflorescências; (iii) maiores porcentagens de simulação de herbivoria nas folhas induzirá uma maior produção de néctar extrafloral nos NEFs foliares; e (iv) néctar extrafloral mais atraente (maior valores de volume e calorias) atrairá mais formigas. O volume de néctar extrafloral e o conteúdo calórico, bem como a abundância de formigas, foram maiores nos NEFs das inflorescências em comparação com os NEFs foliares antes e após a simulação de herbivoria, consistente com uma de nossas previsões. Entretanto, ambos os NEFs foliares e os NEFs de inflorescências, não apenas os das folhas, foram induzidos por simulação de herbivoria, um padrão oposto ao previsto. Plantas submetidas a níveis mais altos de danos nas folhas produziram mais néctar extrafloral e com mais calorias, mas apresentaram abundância similar de formigas. Finalmente, o néctar extrafloral mais atraente atraiu mais formigas. Síntese . Nossos resultados mostram que a produção de néctar extrafloral antes e depois da simulação de herbivoria, bem como o recrutamento de formigas, varia de acordo com a estrutura da planta na qual os NEFs estão localizados. Nosso estudo é o primeiro a mostrar que o recrutamento de formigas por néctar extrafloral segue as previsões da Teoria da Defesa Ótima e que os padrões de forrageamento das formigas podem ser moldados pela parte da planta atacada e pelo nível de dano recebido.